2016
DOI: 10.1128/iai.00717-15
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CD4+Effector Responses by Naturally Occurring CD4+CD25+Foxp3+Regulatory T Cells Contributes to Experimental Cerebral Malaria

Abstract: The role of naturally occurring CD4؉ CD25 ؉ Foxp3 ؉ regulatory T cells (nTreg) in the pathogenesis of cerebral malaria (CM), which involves both pathogenic T cell responses and parasite sequestration in the brain, is still unclear. To assess the contribution and dynamics of nTreg during the neuropathogenesis, we unbalanced the ratio between nTreg and naive CD4 ؉ T cells in an attenuated model of Plasmodium berghei ANKA-induced experimental CM (ECM) by using a selective cell enrichment strategy. We found that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Those cytokines increase the permeability of the blood–brain barrier (BBB) and promote T cells and inflammatory monocytes infiltration which results in brain œdema, axonal damage, and myelin loss [ 3 , 4 ]. Experimental mouse models which utilize Plamodium berghei ANKA ( Pb A) infection of C57BL/6 mice have shown that pathogenic CD4 + and CD8 + T cells, detected in the brain at the onset of neurological symptoms, play a role both at local and systemic levels by contributing to the high levels of TNF-α, IFN-γ and CXCL10 in circulation [ 5 , 6 , 7 ]. The development of CM is associated with recruitment in the brain of CD8 + T cells identified as one of the critical effector cell types mediating human cerebral malaria (HCM) and experimental cerebral malaria (ECM) [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Those cytokines increase the permeability of the blood–brain barrier (BBB) and promote T cells and inflammatory monocytes infiltration which results in brain œdema, axonal damage, and myelin loss [ 3 , 4 ]. Experimental mouse models which utilize Plamodium berghei ANKA ( Pb A) infection of C57BL/6 mice have shown that pathogenic CD4 + and CD8 + T cells, detected in the brain at the onset of neurological symptoms, play a role both at local and systemic levels by contributing to the high levels of TNF-α, IFN-γ and CXCL10 in circulation [ 5 , 6 , 7 ]. The development of CM is associated with recruitment in the brain of CD8 + T cells identified as one of the critical effector cell types mediating human cerebral malaria (HCM) and experimental cerebral malaria (ECM) [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%